Osteogenesis imperfecta in childhood: effects of spondylodesis on functional ability, ambulation and perceived competence - Tolboom, N. (Springer-Verlag, 2003)
We studied the effects of spondylodesis on spinal curvature, functional outcome, level of ambulation and perceived competence in 11 children with osteogenesis imperfecta (OI). Mean age at surgical intervention was 13.1 years (SD 2.5 years) and follow-up amounted to 3.4 years (SD 2.3 years). Spinal curvature was measured according to Cobb. The level of ambulation was scored according to the modified criteria of Bleck. Functional abilities and the amount of parental assistance were scored using the Dutch version of the Pediatric Evaluation of Disability Inventory (PEDI). Perceived competence was measured using the Harter Self-Perception Profile for Children. The amount of fatigue, spinal pain and presence of subjective dyspnea were scored with a visual analog scale. The median progression per year before spondylodesis was 6.1° (interquartile range 2.9°–12.9°) and after the spondylodesis it was 5.0° (interquartile range 1.6°–11.0°). No significant progression or regression in the level of ambulation was found. Perceived competence improved slightly. In the total score of the perceived competence, a borderline significant increase was found (P-value 0.068). We concluded that spinal fusion in children with OI does not materially influence functional ability and level of ambulation. Self-perceived competence seemed to improve after surgery. The amount of pain, fatigue and subjective dyspnea seemed to diminish after spinal surgery. Progression of scoliosis proceeded, as did development of spinal curvature at the junction of the spondylodesis. Therefore, oral or intravenous bisphosphonates before and after spinal surgery should be considered.